Student Engagement in the Digital University : Sociomaterial Assemblages. - Gourlay, Lesley (Routledge, 2018)
"Student Engagement in the Digital University challenges mainstream conceptions and assumptions about students' engagement with digital resources in higher education. While engagement in online learning environments is often reduced to sets of transferable skills or typological categories, the authors propose that these experiences must be understood as embodied, socially situated, and taking place in complex networks of human and nonhuman actors. Using empirical data from a JISC-funded project on digital literacies, this book performs a sociomaterial analysis of student-technology interactions, complicating the optimistic and utopian narratives surrounding technology and education today and positing far-reaching implications for research, policy and practice."--Provided by publisher.